Infection of wheat seed by Pyrenophora triticirepentis - Schilder, A.M.; Bergstrom, Gary Carlton (Canadian Science Publishing, 1994)
The seed infection process of Pyrenophora tritici-repentis, incitant of tan spot of wheat, was investigated, as were several influencing factors. Following inoculation of the wheat spike, P. tritici-repentis gained access to the seed by first colonizing the glume, lemma, or d after inoculation, and palea. Seed infection was first observed 3 infection incidence increased with time and with inoculum concentration. Wheat seeds were susceptible to infection by this fungus throughout most of their development, although inoculation at the milk stage resulted in the highest percentage of infected seeds. Susceptibility to foliar infection by P. tritici-repentis was not a good predictor of susceptibility to seed infection in four wheat cultivars tested in a glasshouse experiment, except perhaps in 'BR 8', which was significantly less susceptible than the other cultivars at early and late stages of seed development. In a field experiment, wheat seed infection by P. tritici-repentis occurred primarily after the early dough stage and was positively correlated with tan spot severity on the flag leaf shortly after anthesis.